Pengaruh Iradiasi Sinar Gamma pada Generasi Pertama (M1) untuk Mendapatkan Genotipe Unggul Baru Kedelai Toleran Kekeringan - WARID WARID; NURUL KHUMAIDA; AGUS PURWITO; MUHAMMAD SYUKUR (Agrotrop : Journal on Agriculture Science, 2017)
Influence of Gamma Rays Irradiation on First Generation (M1) to Obtain New Promising Drought-Tolerance Soybean Genotype. Breeding to produce drought tolerant varieties is one of main strategies in the soybean production improvement. Some limitations in soybean conventional breeding are that it takes long time and that drought tolerant characters are rarely found. Therefore, the improvement of genetic variability is very important to assist drought tolerant. Mutation through gamma irradiation is one of techniques to improve genetic variability. The aims of this research were to obtain LD50, study the influence of irradiation, and genetic of mutation. To determine the LD50, seeds of soybean cv. Anjasmoro were irradiated with 0-800 Gy (100 interval) gamma rays. LD50 was calculated to be 202.5 Gy base on germination rate. Therefore, in further experiment 200-400 Gy (50 interval) dosage were used to irradiate seeds of soybean cv. Anjasmoro and Burangrang. All irradiation dosages (200-400 Gy) damage protoplast, decrease plant survival, prolong flowering dan harvest time, decrease plant height, number of total and filled pod, number of seeds, and improve the number of empty pod.